Classroom video project: an investigation on students perception - Ng, Choo Ting (Elsevier, 2013)
This paper is a preliminary research to understand students “perception on the implementation of video projects into the English language classroom. Data was contributed by thirty-five foundation students from a private university in Selangor. During the beginning of the semester, the participants were assigned to create a short, teenage-themed video clip with the students themselves as the principal actors. Window Movie Maker was used to edit the raw video shot using camcorders. Upon completion of the video project, the students submitted a reflection journal entry to the blog – The English Learning Voyage. These responses were analyzed qualitatively and categorized into four themes: 1) Implementation of the video project; 2) Obstacles faced during the production; 3) Level of satisfaction upon completion of the video; 4) Elements that led to the success of the video project; and 5) Relevance of video project to language learning.